A method for facilitating observation of dispersion state of nanosilica in resin-based material

CN121182142BActive Publication Date: 2026-10-27CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511601925.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-04
Publication Date
2026-10-27
Estimated Expiration
2045-11-04

AI Technical Summary

Technical Problem

但是,由于纳米SiO2与树脂的透明度和折射率相近,导致常规的显微技术难以观察其分散状态,限制了改性树脂基材料的观察与评估

Benefits of technology

[0015]因此,本发明首先将亚甲基蓝染色纳米SiO2,使纳米SiO2在树脂中可视化,并利用常规显微手段观察染色的纳米二氧化硅的分布,成为解决上述问题的关键要素之一;其次,本发明通过改进纳米SiO2的染色方法,具体是对纳米SiO2进行短时间紫外处理,使得亚甲基蓝对纳米SiO2的染色过程高效环保,且染色效果更好,进而使得本发明所述方法能更直观便捷地观察树脂基材料中纳米二氧化硅的分散状态。具体来说,本发明中使用紫外线短时间照射二氧化硅,增加其表面活性,使染料亚甲基蓝分子能更好地吸附在纳米二氧化硅表面,进而提高染色强度。本发明所述方法能为高性能纳米材料改性的树脂基材料的开发提供有力的低成本环保技术支持。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121182142B_ABST
    Figure CN121182142B_ABST
Patent Text Reader

Abstract

The application belongs to the field of resin-based material forming, and particularly relates to a method for conveniently observing the dispersion state of nanometer silicon dioxide in resin-based material, which comprises the following steps: first, nanometer silicon dioxide is placed under ultraviolet light for irradiation for 10-30 min, and stirring is performed several times during the irradiation, so as to form nanometer silicon dioxide treated by ultraviolet irradiation; then, dye methylene blue is dissolved in water, and stirring is performed to form a dyeing solution; a certain amount of NaOH and the nanometer silicon dioxide treated by ultraviolet irradiation are added into the dyeing solution, and stirring is performed to form a mixed solution; the mixed solution is washed with water and ethanol to remove excess dye, and solid-liquid separation is simultaneously performed; the obtained solid is vacuum dried and ground to obtain powder-shaped dyed nanometer silicon dioxide; and then, the dispersion state of the dyed nanometer silicon dioxide in the modified resin after solidification is observed under a microscope. The method can provide powerful low-cost and environment-friendly technical support for the development of resin-based material modified by high-performance nanometer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of resin-based material molding, and specifically relates to a method for easily observing the dispersion state of functional material nano-silica in resin-based materials. Background Technology

[0002] Epoxy resins, polyurethanes, and other resin-based materials are widely used in coatings, composite materials, and other fields due to their excellent processability and chemical stability. However, traditional resins have shortcomings in mechanical strength and thermal stability, making it difficult to meet high-performance requirements. Nano-silica (SiO2), as a functional filler, can significantly improve the mechanical properties and thermal stability of resins, but its high surface energy easily leads to agglomeration, especially during resin curing, which exacerbates the agglomeration phenomenon and affects material properties. Therefore, the key to evaluating the performance of nanomaterial-modified resins lies in how to assess the uniformity of nanomaterials after resin curing. However, because nano-SiO2 has similar transparency and refractive index to resins, conventional microscopic techniques are insufficient to observe its dispersion state, limiting the observation and evaluation of modified resin-based materials.

[0003] Therefore, when studying the dispersion state of functional filler nano-silica in resin-based materials, there is a need to provide a method that facilitates the observation of the dispersion state of nano-silica in resin-based materials. Summary of the Invention

[0004] Silica (SiO2), due to its unique hierarchical porous structure, tunable surface chemical properties, and excellent environmental stability, has become an ideal carrier for functional dyes. Dyed silica is widely used in engineering, chemical, and medical fields due to its non-toxicity, high biocompatibility, and ease of labeling. Methylene blue, as a dye molecule, is characterized by low toxicity and low cost, and is often used to label various nanomaterials. Therefore, this invention first considers using methylene blue-stained nano-silica for observing the dispersion state of nano-silica in resin-based materials.

[0005] However, due to the weak surface interaction between nano-silica and methylene blue, the adsorption efficiency of methylene blue by silica is low, resulting in a small adsorption amount and affecting the dyeing intensity of silica. To address this issue, some researchers have used chemical reagents to modify the silica surface, aiming to enhance the binding ability of nano-silica to the dye methylene blue by introducing specific functional groups; others have subjected silica to prolonged heat treatment after dyeing, hoping to promote the diffusion of dye molecules within the pores or to form a more stable bond with the silica surface through high temperature. However, chemical reagent modification is not only complex but also consumes large amounts of organic solvents and reagents that pose certain environmental risks; while the prolonged heat treatment (120℃, 24h) as described in CN 109233806 B significantly increases the energy consumption and time cost of the process. Therefore, there is an urgent need in this field for a low-cost, rapid, and environmentally friendly method to treat nano-silica to increase its methylene blue dyeing intensity; thereby obtaining a method that facilitates the observation of the dispersion state of nano-silica in resin-based materials.

[0006] This invention provides a method for easily observing the dispersion state of nano-silica in resin-based materials, comprising: Step A, placing nano-silica under a UV lamp for 10-30 minutes, stirring several times during this period, to form UV-treated nano-silica; Step B, dissolving methylene blue dye in water and stirring to form a dyeing solution; Step C, adding a certain amount of NaOH and the UV-treated nano-silica to the dyeing solution and stirring to form a mixed solution; Step D, washing the mixed solution successively with water and ethanol to remove excess dye, while simultaneously performing solidification. Liquid separation; Step E: The obtained solid is vacuum dried and ground to obtain powdered dyed nano-silica; Step F: The dyed nano-silica is added to the resin curing agent and ultrasonically dispersed; Step G: Resin material is added and stirred, and after continued ultrasonic vibration, vacuum degassing is performed to obtain modified resin modified with dyed nano-silica; Step H: The modified resin is heated and cured to obtain cured modified resin; Step I: The dispersion state of dyed nano-silica in the cured modified resin is observed under a microscope, that is, the dispersion state of nano-silica in the resin base material is observed.

[0007] In one specific embodiment, the wavelength of the ultraviolet light emitted by the ultraviolet lamp in step A is 250~258nm, and the nano-silica irradiated under the ultraviolet lamp is stirred 2~5 times.

[0008] In one specific embodiment, the mass ratio of NaOH added to the staining solution in step C to nano-silica treated with ultraviolet irradiation is 1:1~3, and the stirring time to form a mixed solution is 2~5h.

[0009] In one specific implementation, the solid-liquid separation method in step D is vacuum filtration or centrifugation.

[0010] In one specific implementation, the vacuum drying temperature in step E is 50~80℃, and the vacuum drying time is 20min~2h.

[0011] In one specific implementation, the ultrasonic vibration and vacuum degassing times in step G are both 10-30 minutes.

[0012] In one specific embodiment, in step H, after heating and curing to obtain the cured modified resin, it is placed in a freezer for storage, and then thawed at room temperature and under vacuum to obtain a modified resin for microscopic observation of the dispersion state of the stained nano-silica.

[0013] In one specific embodiment, the content of the nano-silica in the resin-based material is 0.2~1.0 wt%.

[0014] In one specific embodiment, the ratio of resin to resin curing agent in the resin-based material is 1:0.5~1.

[0015] Therefore, this invention first dyes nano-SiO2 with methylene blue, making the nano-SiO2 visible in the resin, and then observes the distribution of the dyed nano-silica using conventional microscopic methods, which is one of the key elements in solving the above-mentioned problems. Secondly, this invention improves the dyeing method of nano-SiO2 by subjecting it to short-term ultraviolet treatment, making the dyeing process of methylene blue on nano-SiO2 highly efficient and environmentally friendly, and achieving better dyeing results. This allows for a more intuitive and convenient observation of the dispersion state of nano-silica in resin-based materials. Specifically, this invention uses short-term ultraviolet irradiation of silica to increase its surface activity, allowing methylene blue dye molecules to better adsorb onto the surface of nano-silica, thereby improving the dyeing intensity. The method described in this invention provides strong, low-cost, and environmentally friendly technical support for the development of resin-based materials modified with high-performance nanomaterials. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of ultraviolet-treated nano-silica.

[0017] Figure 2 Excitation spectra of nano-silica obtained by steady-state fluorescence spectroscopy after UV treatment for 20 min, 40 min, and 60 min, and without UV treatment.

[0018] Figure 3Emission spectra of nano-silica obtained by steady-state fluorescence spectroscopy after UV treatment for 20 min, 40 min, and 60 min, and without UV treatment.

[0019] Figure 4 This is a microscope image from Example 4. Detailed Implementation

[0020] Comparative Example

[0021] Dissolve 0.1g of methylene blue in 200ml of water and stir for 5 minutes to form a staining solution. Add 0.5g of commercially available nano-silica and 0.4g of NaOH to the staining solution, and then stir at room temperature for 240 minutes to form a mixed solution. The purpose of adding a small amount of NaOH is to enhance the adsorption of methylene blue by silica. Pour the mixed solution into a vacuum filtration apparatus. First, use 1000ml of deionized water to remove unadsorbed free methylene blue dye. Finally, filter with 100ml of anhydrous ethanol. Alternatively, centrifugation can be used instead of vacuum filtration. Place the filtered and washed silica in a vacuum environment and dry at 50℃ for 60 minutes (or at 80℃ for 20 minutes). Grind the dried block silica into powder using a mortar and pestle to obtain powdered dyed nano-silica. This is nano-silica without UV treatment.

[0022] Example 1

[0023] First, nano-silica was irradiated under a 254nm UV lamp for 20 minutes, with the nano-silica powder stirred every 10 minutes to form UV-treated nano-silica. 0.1g of methylene blue was dissolved in 200ml of water and stirred for 5 minutes to form a staining solution. 0.5g of UV-treated nano-silica and 0.4g of NaOH were added to the staining solution, and the mixture was stirred at room temperature for 240 minutes to form a mixed solution. The mixed solution was poured into a vacuum filtration apparatus. Unadsorbed free methylene blue dye was first removed using 1000ml of deionized water, and finally filtered using 100ml of anhydrous ethanol. The filtered and washed silica was then dried under vacuum at 50℃ for 60 minutes (or 80℃ for 20 minutes). The dried block silica was then ground into powder using a mortar and pestle to obtain powdered dyed nano-silica.

[0024] Example 2

[0025] First, the nano-silica powder was placed under a 254nm ultraviolet lamp for 40 minutes, and stirred every 20 minutes to form ultraviolet-treated nano-silica. The remaining steps were the same as in Example 1.

[0026] Example 3

[0027] First, the nano-silica powder was placed under a 254nm ultraviolet lamp for 60 minutes, and stirred every 30 minutes to form ultraviolet-treated nano-silica. The remaining steps were the same as in Example 1.

[0028] Figure 1 This is a schematic diagram of ultraviolet-treated nano-silica in Examples 1-3. Figures 2-3 The excitation and emission spectra of nano-silica obtained by steady-state fluorescence spectroscopy in Examples 1-3 and the comparative examples after UV treatment for 20 min, 40 min, and 60 min, and without UV treatment, are respectively obtained by testing. Figure 2 and Figure 3 The horizontal axis represents wavelength (nm), and the vertical axis represents intensity (au). Figures 2-3 This serves as a comparative verification of the effects of Examples 1-4. Figure 2 The optimal excitation wavelength was determined to be 350 nm based on the excitation spectrum. Figure 3 The fluorescence intensity under different treatment conditions at an excitation wavelength of 350 nm was shown. The best result was achieved with a 20-minute UV treatment, which increased the maximum fluorescence intensity by 35.92% compared to the untreated sample. This demonstrates that this patented method significantly enhances the fluorescence intensity of methylene blue-stained silica through only a short UV treatment time. Treatments at 40 and 60 minutes, however, resulted in excessive oxidation of the nano-silica surface due to the extended treatment time, leading to structural damage, reduced methylene blue adsorption sites, and consequently, decreased fluorescence intensity.

[0029] Example 4

[0030] Preparation of modified resin: The dyed nano silica obtained in the comparative example and Example 1 were added to the resin curing agent and ultrasonically dispersed for 15 min; then bisphenol A epoxy resin was added and stirred for 10 min, and ultrasonic vibration was continued for 15 min after stirring. Finally, vacuum degassing was performed for 15 min to obtain the modified resin; the nano silica content was 0.5 wt%, and the ratio of bisphenol A resin to resin curing agent was 5:4.

[0031] Heating of modified resin: The modified resin is heated to 90℃ and held at that temperature for 15 minutes to obtain the cured modified resin.

[0032] Storage: Quickly place the heated resin into a freezer for storage.

[0033] Thawing: Thaw the modified resin for 1 hour under vacuum at room temperature.

[0034] Observation of resin: The modified resin after thawing was observed under a microscope, and the results are as follows. Figure 4 As shown, the nano-silica becomes darker in color after 20 minutes of UV treatment. Figure 4 a indicates that this method increases the staining intensity of nano-silica. Figure 4 This is a microscope image from Example 4. Figure 4 a is a dyed nano-silica resin that has been treated with ultraviolet light for 20 minutes. Figure 4 b represents dyed nano-silica resin that has not undergone ultraviolet treatment. Figure 4 As can be seen, the distribution of stained nano-silica in Figures a and b is uneven, but Figure a more clearly shows the distribution state of nano-silica, reducing the weak blue / non-blue silica particles covered by resin, which is beneficial for a more comprehensive evaluation of the distribution state of silica. In summary, this invention provides a method for easily observing the dispersion state of nano-silica in resin-based materials.

[0035] In summary, this invention relates to a method for easily observing the dispersion state of nano-silica in resin-based materials, comprising: firstly, irradiating nano-silica under a UV lamp for 10-30 minutes, stirring several times during this period, to form UV-treated nano-silica; separately, dissolving methylene blue dye in water and stirring to form a dyeing solution; adding a certain amount of NaOH and the UV-treated nano-silica to the dyeing solution and stirring to form a mixed solution; washing the mixed solution successively with water and ethanol to remove excess dye, while simultaneously performing solid-liquid separation; obtaining the solid by vacuum drying and grinding to obtain powdered dyed nano-silica; and then observing the dispersion state of the dyed nano-silica in the cured modified resin under a microscope. The method described in this invention can provide strong, low-cost, and environmentally friendly technical support for the development of high-performance nanomaterial-modified resin-based materials.

[0036] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for easily observing the dispersion state of nano-silica in resin-based materials, characterized in that, include: Step A: First, place the nano-silica under a UV lamp for 10-20 minutes, stirring several times during the process, to form UV-treated nano-silica; the wavelength of the UV light emitted by the UV lamp in Step A is 250-258nm, and the nano-silica under the UV lamp is stirred 2-5 times. Step B: Dissolve methylene blue dye in water and stir to form a dyeing solution; Step C: Add a certain amount of NaOH and the UV-treated nano-silica to the staining solution, and stir to form a mixed solution; the mass ratio of NaOH to UV-treated nano-silica added to the staining solution in step C is 1:1~3, and the stirring time to form the mixed solution is 2~5h; Step D: The mixed solution is washed with water and ethanol successively to remove excess dye, while solid-liquid separation is performed simultaneously; Step E: After vacuum drying and grinding, the obtained solid is used to obtain powdered dyed nano-silica. Step F: Add the dyed nano-silica to the resin curing agent and disperse it by ultrasonication; Step G: Add resin material and stir. The resin material is bisphenol A epoxy resin. After ultrasonic vibration, vacuum degassing is performed to obtain a modified resin modified with dyed nano silica. Step H: The modified resin is heated and cured to obtain the cured modified resin; Step I: Observe the dispersion state of the dyed nano-silica in the cured modified resin under a microscope, that is, observe the dispersion state of nano-silica in the resin-based material.

2. The method for facilitating observation of the dispersion state of nano-silica in resin-based materials according to claim 1, characterized in that, In step D, the solid-liquid separation method is vacuum filtration or centrifugation.

3. The method for facilitating observation of the dispersion state of nano-silica in resin-based materials according to claim 1, characterized in that, In step E, the vacuum drying temperature is 50~80℃, and the vacuum drying time is 20min~2h.

4. The method for facilitating observation of the dispersion state of nano-silica in resin-based materials according to claim 1, characterized in that, In step G, the time for both ultrasonic vibration and vacuum degassing is 10-30 min.

5. The method for facilitating observation of the dispersion state of nano-silica in resin-based materials according to claim 1, characterized in that, In step H, after heating and curing, the cured modified resin is placed in a freezer for storage, and then thawed at room temperature and under vacuum to obtain a modified resin for microscopic observation of the dispersion of stained nano-silica.

6. The method for facilitating observation of the dispersion state of nano-silica in resin-based materials according to claim 1, characterized in that, The content of the nano-silica in the resin-based material is 0.2~1.0 wt%.

7. The method for facilitating observation of the dispersion state of nano-silica in resin-based materials according to claim 1, characterized in that, The ratio of resin to resin curing agent in the resin-based material is 1:0.5~1.

Citation Information

Patent Citations

  • A method for preparing methylene blue-containing silica particles with high fluorescence intensity using heat treatment-assisted preparation.

    CN109233806B

  • Nanoparticles containing dyes and process for immobilizing dye particles in nanoparticles.

    BR102018016867A2

  • Method for improving dye light resistance

    CN105925009A